A technique for introducing looped sutures in flexor tendon repair - Kamath B Jagannath; C. Ramanathan (Indian Journal of Plastic Surgery)
This is the author′s experience of hypospadias reconstruction using Bracka′s technique (mainly) over a period of three years. A total of 98 procedures related to hypospadias were done in three years. The surgical technique is described. In the author′s hand, Bracka′s technique gives good result both functionally and in appearance. Its versatility enables its use in all types of hypospadias with consistently reproducible results with minimal complications. At the end of the second stage a circumcised penis with natural looking vertical slit neo-meatus at the apex of the glans is produced.